(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
As the universities across the country shifted to online instruction in March 2020, faculty development program administrators faced challenges in providing authentic and useful pedagogical resources to their already overwhelmed instructors. This one-person case study explores a new mode of professional development which engages a faculty member in sustained, personal communications to support his disciplinary writing online course development. Both trauma-informed and relationship-centered, this alternative professional development model featured real-time reflection which resulted in high quality pedagogical adjustments to one disciplinary literacy instructor’s newly online course.